An Improved Dynamic Voltage Restorer Model for Ensuring Fault Ride-Through Capability of DFIG-based Wind Turbine Systems (ELEKTRIKA- Journal of Electrical Engineering, 2020)
Renewable energy sources (RES) are being integrated to electrical grid to complement the conventional sources in meeting up with global electrical energy demand. Among the RES, Wind Energy Conversion Systems (WECS) have gained global electricity market competitiveness especially the Doubly Fed Induction Generator (DFIG)-based Wind Turbines (WTs) because of flexible regulation of active and reactive power, higher power quality, variable speed operation, four quadrant converter operation and better dynamic performance. Grid connected DFIG-based WTs are prone to disturbances due to faults in the network which made the utilization of the power generated a major concern. The grid code requirement for integrating the DFIGs to grid specified that they must remain connected and support the grid stability during grid disturbances of up to 1500milliseconds. The ability of the DFIG WT system to uphold to the grid codes requirement is termed the Fault Ride – Through (FRT). This paper presented a 1.5MW grid connected DFIG-based WT model with a Dynamic Voltage Restorer (DVR) for FRT capability enhancement. The design and simulation were performed in MATLAB/Simulink software. The test system was subjected to disturbances leading to Low Voltage Ride – Through (LVRT), Zero Voltage Ride – Through (ZVRT) and High Voltage Ride – Through (HVRT) considering three – phase balanced fault and single line to ground fault. The performance of improved model of DVR shows enhancement over conventional DVR in terms of voltage compensation and fault current mitigation.
Keywords: Doubly Fed Induction Generator; Dynamic Voltage Restorer; Fault Ride – Through; IEEE519 Standard; Wind Energy Conversion System.